1996
DOI: 10.1063/1.868866
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of wake turbulence with a free surface

Abstract: The turbulent wake of a flat plate aligned with a uniform water flow and extending through the free surface was investigated experimentally. Laser-Doppler velocimetry (LDV) measurements show good agreement with published data for a two-dimensional wake, except in a shallow layer near the free surface. In this surface layer, the wake width is observed to double while the wake centerline velocity remains essentially unchanged from its value at depth, resulting in a wake momentum deficit that is twice that at dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…The range of the signed swirling strength magnitude decreases mildly from the mid-depth to the near-surface location. This is probably due to the appearance of structures parallel and close to the free surface, as found by Logory et al (1996). The origination of these structures may contribute to the reduction of the swirling strength magnitude close to the free surface.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The range of the signed swirling strength magnitude decreases mildly from the mid-depth to the near-surface location. This is probably due to the appearance of structures parallel and close to the free surface, as found by Logory et al (1996). The origination of these structures may contribute to the reduction of the swirling strength magnitude close to the free surface.…”
Section: Resultsmentioning
confidence: 89%
“…Amongst other observations, he found that vortices from the separating shear layer grow in the near-wake region, but starts to dissipate due to the bed friction effect at the intermediate and far-wake regions. The effect of free surface on the wake structure was explored by Logory et al (1996) and Maheo (1999). The free surface was mainly found to be characterized by 'upwelling' and 'downdraft' type of events.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the free-surface velocity field induced by the oblique interaction of a vortex ring with the surface have been reported by Weigand [138]. A similar approach was used by Logory et al [89] in their work investigating the free-surface wake behind a vertical flat plate. Both of these studies report illuminating laser light sheets within 1 mm of the free surface, the thickness of the sheets also being approximately 1 mm.…”
Section: Introductionmentioning
confidence: 85%
“…In the outer region, the flow is up towards the free surface and out away from the wall which thickens the boundary layer near the free-surface. Apart from these studies, there are two other experimental studies, namely [3,28]. While the measurements of Logory et al [28] are taken in wake of surface-piercing flat-plate, the measurements of Longo et al [3] are for both boundary layer and wake.…”
Section: 22mentioning
confidence: 99%